An investigation of Spur’s integration of a plant-based menu and how it influences their brand identity and brand image among conscious consumers - Kluyts, André (The IIE, 2020)
Based on the growth of conscious consumerism, brands are under pressure to adapt their operations and offerings, which presents a problem in the potential development of a gap between their brand identity and brand image, because it can lead to a negative reputation and poor market performance. This study investigates this problem within the context of Spur‟s integration of a plant-based menu. The purpose of this study is to investigate Spur‟s integration of a plant-based menu and how it influences the potential gap between their brand identity and brand image among conscious consumers, against Kapferer‟s (2008) brand identity prism. A qualitative, phenomenological and cross-sectional design was implemented. Furthermore, two data collection methods, a focus group and in-depth interview, were utilised and the data was analysed by means of a thematic content analysis. Spur‟s integration of a plant-based menu influenced an overall reduction in the gap between Spur‟s brand identity and brand image among conscious consumers. This finding contributes to the brand identity and brand image literature within a South African restaurant context, which was found to be an area that has rarely been studied.
Keywords: Brand image; Conscious living; Environmental sustainability; Sustainability; Vegan; Vegetarian; Restaurant industry; Conscious consumerism